1994
DOI: 10.1002/j.1460-2075.1994.tb06702.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for a zinc motif for template recognition by the bacteriophage T7 primase.

Abstract: Gene 4 of bacteriophage T7 encodes two proteins, a 63 kDa and a colinear 56 kDa protein. The coding sequence of the 56 kDa protein begins at the residues encoding an internal methionine located 64 amino acids from the N‐terminus of the 63 kDa protein. The 56 kDa gene 4 protein is a helicase and the 63 kDa gene 4 protein is a helicase and a primase. The unique 7 kDa N‐terminus of the 63 kDa gene 4 protein is essential for primer synthesis and contains sequences with homology to a Cys4 metal binding motif, Cys‐X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 50 publications
(11 reference statements)
7
110
0
3
Order By: Relevance
“…Four highly conserved cysteine residues within the ZBD coordinate a zinc atom that is undoubtedly important for protein folding (15). These cysteines were not mutated because the bound metal is required for the interaction of the primase with the DNA template (31). We confirmed by CD spectroscopy that the alanine scanning mutants of the ZBD are folded and yield a CD spectrum similar to that of the wild-type ZBD.…”
Section: T7 Primase-polymerase Complexmentioning
confidence: 72%
“…Four highly conserved cysteine residues within the ZBD coordinate a zinc atom that is undoubtedly important for protein folding (15). These cysteines were not mutated because the bound metal is required for the interaction of the primase with the DNA template (31). We confirmed by CD spectroscopy that the alanine scanning mutants of the ZBD are folded and yield a CD spectrum similar to that of the wild-type ZBD.…”
Section: T7 Primase-polymerase Complexmentioning
confidence: 72%
“…3). By analogy to the phage T7 gene 4 product (gp4), the motif might be involved in Zn 2ϩ binding and play a role in primase activity (6,37,41). In another region of gp␣, an amino acid sequence (positions 501 to 508; GPGGSGKS) matches the type A NBS found in other DNA helicases (20,61).…”
Section: Resultsmentioning
confidence: 99%
“…This could be tested by using an N-terminal gp␣ peptide variant of gp␣⌬2 carrying a mutation in the proposed metal ion-binding cluster. The T7 gene 4 protein (63 kDa, 567 residues) combines two functions, primase and helicase, within one polypeptide chain, which are probably organized as two functional and structural domains (37,38). The primase domain resides in the N-terminal and the helicase in the C-terminal portion, as was suggested by sequence comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of the zinc motif of the primase of Bacillus stearo-thermophilus has shown that it is a member of the zinc ribbon subfamily of zinc binding motifs such as that found in the yeast RNA polymerase II subunit 9 (22). Gene 4 protein contains 1 g atom of zinc per mole of gene 4 protein (26). In vitro mutagenesis of residues in this region as well as studies with chimeric T7 primases have demonstrated a role of the zinc motif in recognition of the trinucleotide sequence 5Ј-GTC-3Ј (27,28).…”
mentioning
confidence: 99%